KEEFEKTIFAN PEMBELAJARAN MELALUI MODEL GROUP INVESTIGATION BERBANTU MEDIA FLASHCARD TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Henry Januar Saputra, Lisa Andarwati, Ikha Listyarini (Universitas PGRI Yogyakarta, 2018)
The purpose of this study is to determine effectiveness Learning Group Investigation Model Flashcard Media Helped Science Learning Results Material Resources Energy StudentClass III SDN Sawah Besar 01 Semarang. This type of research is quantitative research in theform of True Experiment Design. The population in this study is the overall grade 3 studentsSDN Sawah Besar 01 Semarang. The samples taken are 40 students from each class. ClassControl using Simple Random Sampling technique. The research design used is PretestPosttestControlGroupDesign.Thisresearchdataisobtainedthroughresearchinstrumentofpretest,posttest,documentation,test,interview.Basedontheanalysisresultof learningresultofcontrolclassandexperimentclassbyusingresultofttestcalculationobtainedtct=6,026.Fromthe t distribution list with dk = 40 + 40 - 2 = 78 we get 1.991. Because tcount 6.026>1,991 ttable then Ho is rejected, so it can be concluded that the average learning result ofexperimental class (82,1) is bigger than control class (70,6). Based on the results of classicalcompletion of learning in the experimental class after being given treatment using learningmodel group investigation assisted flashcard media obtained 95% learning mastery score, compared to control class only get 60%. So it can be concluded that the model of study groupinvestigation assisted flashcard media on the learning outcome of science class energyresources class III SDN Sawah Besar 01 Semarang effective.Keywords: group investigation, flashcard, learning result